Would information acquisition increase enterprises’ willingness to participate in the carbon market? An empirical investigation of equipment manufacturing enterprises in Henan Province, China - Ma, Xin; Xv, Fan; Ge, Rubing; Chen, Tengfei; Cui, Caocao; Lv, Qi (Frontiers in Environmental Science, 2022)
The carbon market is the most important policy tool for achieving carbon peak and carbon neutralization. Enterprises are significant players in the carbon market, and this study aimed to identify if their willingness to participate is connected to the carbon market’s stability and, at the same time, whether it is also relevant for policy design and implementation. Using the technology acceptance model (TAM) and 226 questionnaire data from equipment manufacturing enterprises in Henan Province, China, this study contributes to the empirical analysis of the impact mechanism of information acquisition on the enterprises’ willingness to participate in the carbon market, with a particular focus on evaluating the three main transmission paths: the mediating role of perceived ease of use, the mediating role of perceived usefulness, and the chain mediating role of perceived ease of use and perceived usefulness; moreover, the results of the robustness tests also confirmed the soundness and validity of the research model. The study underlined that when appropriately designing the incentive mechanism for enterprises to participate in the carbon market, it may effectively enhance their willingness to participate in the carbon market by improving their perception of the ease of use and usefulness of the carbon market.